The Chancellor of the Inquisition marking the Incorrigibles. - Gillray, James, 1756-1815 (Humphrey, H., 1793)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Great Britain -- Politics and government -- 1760-1820; Sheridan, Richard Brinsley, 1751-1816